Review on the physicochemical properties of perovskite as catalysts for water and wastewater treatment / Puteri Nurhayani Asmadi, Rasyidah Alrozi and Dr Norhaslinda Nasuha - Asmadi, Puteri Nurhayani; Alrozi, Rasyidah; Nasuha, Norhaslinda (2020)
The main objective of this study is to review the physico-chemical investigations of perovskite catalyst on water and wastewater treatment. Advanced Oxidation Process (AOP) method treat the organic contamination effluent from industry that uses organic components or elements by generated highly oxidizing hydroxyl radicals (HO.). The general formula of perovskite catalyst is ABO3 where A-site is a type of rare earth metal while B-site is a transition metal which known to be heterogeneous catalyst that help to degrade the organic effluent under dark ambient conditions. This comparative study compares the performance of catalytic activity of perovskite catalyst based on its physicochemical properties. The scope of work on overall paper determine the percentage of degradation of organic pollutants which correlated to the perovskite's physicochemical properties. The research methodology used the data collection and analyzed them in the previous study to fulfill the research on the study by putting together all notable related journals, past studies and research works done. Therefore, the study of perovskite catalyst is analyzed by using scanning electron microscopy (SEM), Transmission Electron Micrographs (TEM), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and Texture profile analysis (TPA). As a result, perovskite catalyst is very effective in degrading methyl orange under dark ambient condition from low 10 ppm to high 100 ppm concentrations between 20-90 minutes, thus generating electrons which reacted with dissolved O2 in the solutions to yield reactive species such as HO• for further degradation and mineralization. The perovskite catalyst have an active surface of catalyst that can help fasten the degradation of organic in wastewater by adsorption of organic onto the active surface of perovskite catalyst. Therefore, it is considered stable under the oxidative conditions and their thermal stability was better for the possible used on organic wastewater treatment.